(untitled) (Malaysian Management Journal, 1999)
A sample of 224 companies listed in the Kuala Lumpur Stock Exchange was taken for the period 1991-96. The serial correlations tests of varying lags and the runs tests were employed to test for the random walk theory. The bulk of the results tilts towards the rejection of non-randomness, lending weight to the argument that the stock market has no memory, and casting doubt upon the usefulness of technical analysis.